ω-Al2O3“ a microcrystalline ordered form of transition spinel alumina metastable up to 1200 ​°C - Wallez, Gilles (Journal of solid state chemistry, 2022)
A new variety of alumina with micron-sized crystallization was obtained in mixture with other phases (a Si-doped transition alumina, α-Al2O3 and small amounts of mullite) by firing an Al2O3:SiO2 (12:1) gel at 1200 ​°C, beyond the domain of existence of the heretofore known transition aluminas. The so-called ω-Al2O3 transforms very slowly into α-Al2O3, even at such temperatures. According to X-ray diffraction /Rietveld analysis, the ordered orthorhombic (space group P21212) crystal structure corresponds to a 1 ​× ​1.5 ​× ​1 superstructure of the cubic spinel cell, with a 50 % deficiency in the occupancy of the octahedral sites in 1/3rd of the (010) layers. Though many arguments are in favor of a pure - or almost pure - form of alumina, no evidence can be given of the absence of silicon. The 3-layer sequence of new ω-Al2O3 results from the insertion of a cation-deficient octahedra layer into the usual spinel array. [Display omitted] •A new variety of micron-sized alumina.•Long-time metastability up to 1200 ​°C.•A novel form of fully ordered cation-deficient spinel structure.